Hydrogen adsorption on graphane: An estimate using ab-initio interaction. (13th April 2017) - Dicko, M.; Seydou, M.; Darkrim Lamari, F.; Langlois, P.; Maurel, F.; Levesque, D.
Abstract: The interaction between hydrogen molecule and graphane, material synthesized when a graphene plane is fully functionalized by hydrogen atoms, is assessable by quantum mechanical ab-initio calculations. Therefore for hydrogen, it is possible to estimate the adsorption properties of a porous material similar to activated carbons, the adsorbent surface of which is made of graphane planes instead of graphene or basal graphitic planes. The calculation realized by Monte-Carlo simulations in the grand canonical ensemble shows that the hydrogen adsorption of graphane stays qualitatively similar to that of graphene. Highlights: Adsorption properties of functionalized graphene: the graphane. Accurate ab-initio estimate of interaction between hydrogen molecule and graphane. Determination up to high pressures of adsorption capacity for hydrogen of graphane.